Complex context relationships between DNA methylation and accessibility, histone marks, and hTERT gene expression in acute promyelocytic leukemia cells: perspectives for all‐trans retinoic acid in cancer therapy. Issue 6 (22nd April 2020) - Garsuault, Delphine; Bouyer, Claire; Nguyen, Eric; Kandhari, Rohan; Prochazkova‐Carlotti, Martina; Chevret, Edith; Forgez, Patricia; Ségal‐Bendirdjian, Evelyne
Abstract : Telomerase (hTERT) reactivation and sustained expression is a key event in the process of cellular transformation. Therefore, the identification of the mechanisms regulating hTERT expression is of great interest for the development of new anticancer therapies. Although the epigenetic state of hTERT gene promoter is important, we still lack a clear understanding of the mechanisms by which epigenetic changes affect hTERT expression. Retinoids are well‐known inducers of granulocytic maturation in acute promyelocytic leukemia (APL). We have previously shown that retinoids repressed hTERT expression in the absence of maturation leading to growth arrest and cell death. Exploring the mechanisms of this repression, we showed that transcription factor binding was dependent on the epigenetic status of hTERT promoter. In the present study, we used APL cells lines and publicly available datasets from APL patients to further investigate the integrated epigenetic events that promote hTERT promoter transition from its silent to its active state, and inversely. We showed, in APL patients, that the methylation of the distal domain of hTERT core promoter was altered and correlated with the outcome of the disease. Further studies combining complementary approaches carried out on APL cell lines highlighted the significance of a domain outside the minimal promoter, localized around 5 kb upstream from the transcription start site, in activating hTERT. This domain is characterized by DNA hypomethylation and H3K4Me3 deposition. Our findings suggest a cooperative interplay between hTERT promoter methylation, chromatin accessibility, and histone modifications that force the revisiting of previously proposed concepts regarding hTERT epigenetic regulation. They represent, therefore, a major advance in predicting sensitivity to retinoid‐induced hTERT repression and, more generally, in the potential development of therapies targeting hTERT expression in cancers. Abstract : Telomerase (hTERT) reactivation is a key event in oncogenesis. Although the epigenetic‐based regulation of hTERT is important, we still lack a clear understanding of the mechanisms by which epigenetic changes affect hTERT gene promoter. Our findings suggest a cooperative interplay between hTERT promoter methylation, chromatin accessibility, and histone modifications that force the revisiting of previously proposed concepts regarding hTERT regulation.